2017
DOI: 10.3991/ijim.v11i3.6605
|View full text |Cite
|
Sign up to set email alerts
|

Android Users Privacy Awareness Survey

Abstract: Abstract-Having a share of over 80% of the smartphone market, Android has become an important mobile operating system that is used by billions of users on daily basis. With the widespread use of smartphones in general, and Android in specific, privacy concerns grow with that expansion in the user base. With the millions of applications being downloaded by users daily, it is becoming increasingly difficult to differentiate between the good and the bad in terms of security and privacy. In this paper, we present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Privacy and secrecy issues also have been highlighted in mobile apps/systems in education and business domains [23], [24]. In 2017 a survey on awareness of privacy has been conducted among Android users, which revealed that the level of understanding is still low [25] even though there is a raising need for privacy.…”
Section: Related Workmentioning
confidence: 99%
“…Privacy and secrecy issues also have been highlighted in mobile apps/systems in education and business domains [23], [24]. In 2017 a survey on awareness of privacy has been conducted among Android users, which revealed that the level of understanding is still low [25] even though there is a raising need for privacy.…”
Section: Related Workmentioning
confidence: 99%
“…This application has successfully passed the standard screening process to ensure the security and privacy of the users through Google Play Protect [26]. Unlike most of the applications downloaded from the play store, "SuperWomen" does not contain any advertisement which reduces user concerns regarding adware that can threaten their privacy and mobile system security [27].…”
Section: Application Deployment and Feedbackmentioning
confidence: 99%
“…Alani [11] noted that android smartphone privacy awareness concern grow with spread in users" perspective. A huge number of apps are downloaded daily by the users, but it is really difficult to differentiate between good terms of service security apps and bad terms of service security apps.…”
Section: Previous Workmentioning
confidence: 99%